Ahead of his time: Joseph Grinnell, natural history, and inclusion and equity in STEM - Ribble, David O. (THERYA, 2022)
Joseph Grinnell designed the Natural History of the Vertebrates (NHV) course at the Museum of Vertebrate Zoology, University of California at Berkeley, over 100 years ago and the course has changed little over these years. In this essay, I connect modern pedagogical and cognitive understandings of what we know leads to success among students to the course. This analysis reveals that the course continues to be successful because it has all the elements of a student-centered, active-learning class that leads to better cognitive gains, better retention, and importantly, proportionately better gains for students from underserved populations. This study will be important for advocates of teaching natural history in biology curriculum.